Congress volume : Leuven, 1989 - Emerton, John Adney. (Supplements to Vetus Testamentum, 1991)
This volume publishes twenty-three papers given by invitation at the thirteenth Congress of the International Organization for the Study of the Old Testament, which was held at Leuven from 27 August until 1 September 1989 under the Presidency of C. Brekelmans. The articles cover a range of subjects relevant to the Old Testament: the Pentateuch (E.W. Nicholson, W.H. Schmidt, E. Blum, J. Van Seters, A. de Pury), the historical books (C. Brekelmans, Helga Weippert, R.D. Nelson, W. Thiel, Sara Japhet, K.-F. Pohlmann), the prophets (C. Hardmeier, D.L. Petersen, W.A.M. Beuken, R.P. Carroll, P.-M. Bogaert), the Psalms (J. Trublet, N. Füglister), textual criticism (E. Tov), the Targums (L. Díez Merino), the development of Israelite religion (N.P. Lemche), the Babylonian New Year Festival and the Old Testament (K. van der Toorn), and the Apocryphon of Jannes and Jambres (A. Pietersma).